The Study on Dual Fuel Spray and Characteristics of Combustion of Diesel, Natural Gas and Dual Fuel - Abdalla Tasneem; Wang Qian; Xiaoqiang Tan (Journal of Energy Conservation, 2018)
Combustion of fossil fuels provides around 88% of total energy supply for modern society, and meanwhile causes many environ mental problems and social problems such as air pollution and energy crisis. Therefore，both at home and abroad are focusing on the research and development of natural gas engine recently. However, the mass production and application of this kind of engine are restricted by some unsolved technical difficulties. This paper explored the injection, combustion and emission processes of diesel/ natural gas and dual fuel engine based on Chemkin II, Fire software and Schlieren method. The experimental study on the mixing process of dual fuel jet was carried out by using high-speed Schlieren method in a constant volume bomb. Based on the Fire software, and then applied to Chemkin II software to analyze the effect of the initial temperature and pressure on the net heat production and combustion emissions. The results show that Dual fuel mechanism is capable of producing different heat production behaviors when varying the initial pressure and temperature CO2 emissions are minimized by changing the initial pressure above or below the atmospheric value. However, CO emissions are peaked when diesel fuel is used. The dual fuel engine minimizes the CO emissions amount caused by diesel fuel. Increasing the initial pressure eliminates dual fuel CO2 combustion emissions. The research of this paper is important to optimize the in cylinder combustion processes of natural gas engine, and have a certain important meaning to guide the development of diesel ignition dual fuel engine.
Keywords: Chemkin II